... Of Memories and Realization ... - Bajracharya, Saroj (SIRJANĀ – A Journal Of Arts and Art Education, 2016)
Art is about looking for someone that you think you know, in an invisible crowd. This invisible crowd has its own characteristics… and people around think that you are building those characteristics or imagining them. But it is not only imagination; it actually exists because you exist. Therefore, that invisible crowd that reflects outside is in fact inside of you and vice versa i.e. who you are looking for is also looking for you. The day you find each other is the day you become an artist; then onward, no second person has to verify that you are an artist.